MAPPING THE SCHOOL: THE MAIN ENTRANCE AND THE STRATEGY OF INSIDE TRAJECTORIES - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2015)
The article deals with the general school culture, the specifity of its space and how it depends on administrators’ and teachers’ decisions to turn students’ movement for an easier control of them and the appropreate teaching conditions. Using the theories of H. Lefebvre, M. de Certeau, G. Deleuze and F. Guattari, it is shown how differently the space is understood, and where “the 3rd space” appears. Usually it created by students themselves for their living at school. The main focus is put on the main school entrance – doors as the crack for the flowing streams from outside to inside and vice versa, for the deterritorization (Deleuze, Guattari) of school life and bringing new inspirations into the framed school culture. The illiustration of such a process of school life is presented by an empirical research on school cultures, which was done in 2014–2015 in six Lithuanian general schools. The data show how administrators and teachers treat the main school entrance-free or as a controlled streaming of students through it, and how students treat this control at the door, also what alternative space is created by students as a consequence of administrators’ control.